Identification of Pithomyces chartarum causing leaf spot of cabbage in Malaysia - Nasehi, Abbas; Kadir, Jugah; Ashtiani, Farnaz Abed; Esfahani, Mehdi Nasr; Golkhandan, Elham; Nyaka Ngobisa, A. I. C. (Taylor & Francis, 2014)
A leaf spot disease was observed on cabbage (Brassica oleracea L. var. capitata) affecting 80% of plants growing in greenhouses and fields in Serdang, Selangor, Malaysia. Symptomatic leaf samples were collected from infected plants and isolations made on agar medium. Single-spore isolates from resulting colonies were identified based on cultural and morphological characteristics as Pithomyces chartarum. Morphological identification was confirmed by sequence analysis of the internal transcribed spacer (ITS) regions 1 and 2, including 5.8S rDNA (ITS1-5.8S-ITS2). Pathogenicity tests indicated that P. chartarum causes leaf spot on cabbage. This is the first report of leaf spot caused by P. chartarum on cabbage in Malaysia.